An approach to uncover the relationship between 17b-estradiol and ESR1/ESR2 ratio in the regulation of canine corpus luteum - Bonfim Neto, Antenor Pereira; Cardoso, Ana Paula Mattoso Miskulin; Silva, Renata dos Santos; Sousa, Liza Margareth Medeiros de Carvalho; Giometti, Ines Cristina; Binelli, Mario; Bauersachs, Stefan; Kowalewski, Mariusz Pawel; Papa, Paula de Carvalho (Frontiers in Veterinary Science, 2022)
The canine corpus luteum (CL) is able to synthetise, activate and deactivate 17b-estradiol (E2) and also expresses nuclear estrogen receptors in a time-dependent manner during diestrus. Nevertheless, we are still missing a better comprehension of E2 functions in the canine CL, especially regarding the specific roles of estrogen receptor alpha (ERa) and ERb, encoded by ESR1 and 2, respectively. For that purpose, we analyzed transcriptomic data of canine non-pregnant CL collected on days 10, 20, 30, 40, 50 and 60 of diestrus and searched for differentially expressed genes (DEG) containing predicted transcription factor binding sites (TFBS) for ESR1 or ESR2. Based on biological functions of DEG presenting TFBS, expression of select transcripts and corresponding proteins was assessed. Additionally, luteal cells were collected across specific time points during diestrus and specificity of E2 responses was tested using ERa and/or ERb inhibitors. Bioinformatic analyses revealed 517 DEGs containing TFBS, from which 67 for both receptors. In general, abundance of predicted ESR1 targets was greater in the beginning, while abundance of ESR2 targets was greater in the end of diestrus. ESR1/ESR2 ratio shifted from an increasing to a decreasing pattern from day 30 to 40 post ovulation. Specific receptor inhibition suggested an ERa-mediated positive regulation of CL function at the beginning of diestrus and an ERb-mediated effect contributing to luteal regression. In conclusion, our data points toward a broad spectrum of action of E2 and its nuclear receptors, which can also act as transcription factors for other genes regulating canine CL function.